Leisure-time Physical Activity in Pregnancy and the Birth Weight Distribution: Where is the effect? - Mudd, Lanay M. (2011)
BACKGROUND: Leisure-time physical activity (LTPA) is recommended during pregnancy and has been associated with lower risk of delivering a large infant. We sought to characterize the effect of LTPA across the entire birth weight distribution. METHODS: Women enrolled in the Pregnancy Outcomes and Community Health (POUCH) Study (1998–2004) were followed-up in 2007. Follow-up efforts were extensive for a subcohort and minimal for the remainder (non-subcohort). Thus, 596 subcohort and 418 non-subcohort women who delivered at term participated. Offspring were categorized as small-, appropriate-, or large-for-gestational-age (SGA, AGA, and LGA, respectively) based on gender and gestational age-specific birth weight z-scores (BWz). At follow-up, women recalled pregnancy LTPA and were classified as inactive, insufficiently active or meeting LTPA recommendations. Linear, logistic, and quantile regression analyses were conducted separately by subcohort status. RESULTS: Meeting LTPA recommendations decreased odds of LGA significantly among the non-subcohort (aOR=0.30, 95%CI: 0.14–0.64) and non-significantly among the subcohort (aOR=0.68, 95%CI: 0.34–1.34). In quantile regression, meeting LTPA recommendations reduced BWz among the upper quantiles in the non-subcohort. CONCLUSIONS: LTPA during pregnancy lowered odds of LGA and reduced BWz among the upper quantiles, without shifting the entire distribution. LTPA during pregnancy may be useful for reducing risks of large fetal size.